The Effect of Nature Connectedness on Cognitive Functions and Perceived Stress: A Gender-Based Analysis - Manya Shukla; Smriti Sethi (International Journal of Education Sciences, 2026)
In today’s fast-paced world, young adults face increasing cognitive demands and heightened stress levels due to academic, professional, and social pressures. At the same time, modern lifestyles have ledto a decline in meaningful interactions with nature, which may impact both cognitive function and stressmanagement. The present study, entitled "The Effect of Nature Connectedness on Cognitive Functions and Perceived Stress: A Gender-Based Analysis," aimed to explore the effects of nature connectedness on perceived stress, and cognitive functions while examining gender differences. A sample of 100 participants (50 males and 50 females) completed the Nature Connectedness Scale, Perceived Stress Scale, and a cognitive function assessment. The findings revealed significant gender differences, with females reporting higher levels of nature connectedness (M = 51.26, SD = 5.50) and better cognitive functions (M = 48.32, SD = 16.87) compared to males (M = 48.92, SD = 7.36 and M = 41.70, SD =13.99, respectively). Contrary to expectations, the relationship between nature connectedness and cognitive functions was weak and negative for both genders, reaching statistical significance only among females (r = -.279, p < .05). Additionally, a weak but significant negative correlation between nature connectedness and perceived stress was found among females (r = -.272, p < .05), while no significant relationship was observed in males. Regression analysis indicated that nature connectedness was a significant predictor of cognitive function in females (B = -0.857, p = .050, R² = 0.078) but did not predict perceived stress in either gender. These findings suggest that while females exhibit greater nature connectedness and cognitive performance, the anticipated positive relationship between nature connectedness and cognitive functions is not supported. The study highlights gender-specific patterns in how nature connectedness influences psychological outcomes and underscores the need for future research to explore additional variables and longitudinal designs to fully understand these complex relationships.
Keywords: Cognitive Functions; gender differences; nature connectedness; perceived stress; psychological outcomes